V.l.n.r. zittend: Hartog, Wibaut, Ribbius, ?; staand: Secrève, Albarda (?), Vries-Bruins, ?. Geschenk van W. Drees (1926)
V.l.n.r. zittend: Hartog, Wibaut, Ribbius, ?; staand: Secrève, Albarda (?), Vries-Bruins, ?. Geschenk van W. Drees.